Biodiversity of Vegetable Crops, A Living Heritage - Santamaria, Pietro (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Intensive agriculture has generally resulted in higher productivity, but also in a trend towards decreasing levels of agro-biodiversity, which represents a key point in ensuring the adaptability and resilience of agro-ecosystems in the global challenge to produce more and better food in a sustainable way. The biodiversity of vegetable crops includes genetic diversity-both as species diversity (interspecific diversity) and as a diversity of genes within a species (intraspecific diversity) with regard to the vegetable varieties grown-and the diversity of agro-ecosystems (agro-biodiversity). The purpose of this Special Issue is to publish high-quality research papers addressing recent progress and perspectives on different aspects related to the biodiversity of vegetable crops. Original, high-quality contributions that have not yet been published, or that are not currently under review by other journals have been sought. The papers in this Special Issue cover a broad range of aspects and report recent research results regarding agro-biodiversity, which continues to be of significant relevance for both genetic and agricultural applications. All contributions are of significant relevance and could stimulate further research in this area.